Effectiveness of the credit-line approach for support of CD4 equipment functionality in northern Uganda - Michael L. Kasusse; Nazarius M. Tumwesigye; Steven Aisu; Joseph K.B. Matovu; Rhoda Wanyenze (AOSIS, 2015)
Background: Improving laboratory service delivery requires a functioning logistics and supply system. Uganda's Ministry of Health uses the credit-line approach to provide laboratory supplies including commodities for CD4 test equipment. Objectives: We examined the effectiveness of the credit-line approach in improving laboratoryservice delivery by using the functionality of CD4 test equipment as a proxy indicator. Method: A cross-sectional survey was conducted at 7 level-three health centres (HC IIIs), 18 level-four health centres (HC IVs), and 10 hospitals in 15 districts of mid-northern Uganda, including the Lango (17 facilities) and Acholi sub-regions (18 facilities), between July 2013 and August 2013. Functionality, was determined through self- and interviewer-administered questionnaires. The chi-squared test was used to assess differences in functionality by subregion, facility type, and equipment type. Results: A total of 38 CD4 test analysers were assessed. Of these, 26 (68%) were functional. In hospitals, 85% of CD4 analysers were functional, in HC IVs, 67% were functional and in HCIIIs, 43% were functional. The differences did not reach statistical significance. In the Langosub-region, 72% of analysers were functional; in the Acholi sub-region, 65% were functional. Non-functionality was mainly due to lack of reagents and cartridges, as well as low staffing levels of laboratory technicians with the skills necessary to operate the equipment. Conclusion: The credit-line approach supported the functionality of CD4 equipment in the surveyed facilities. However, there is a need to address issues of staffing and availability of reagents to enhance the functionality of CD4 equipment and improve patient care, especiallyat HC IIIs.